Spatiotemporal spread of chikungunya virus in Sarawak, Malaysia. (30th March 2021) - Dass, Sarat; Ngui, Romano; Gill, Balvinder Singh; Chan, Yoke Fun; Wan Sulaiman, Wan Yusoff; Lim, Yvonne Ai Lian; Mudin, Rose Nani; Chong, Chee Kheong; Sulaiman, Lokman Hakim; Sam, I-Ching
Abstract: Background: We studied the spatiotemporal spread of a chikungunya virus (CHIKV) outbreak in Sarawak state, Malaysia, during 2009–2010. Methods: The residential addresses of 3054 notified CHIKV cases in 2009–2010 were georeferenced onto a base map of Sarawak with spatial data of rivers and roads using R software. The spatiotemporal spread was determined and clusters were detected using the space-time scan statistic with SaTScan. Results: Overall CHIKV incidence was 127 per 100 000 population (range, 0–1125 within districts). The average speed of spread was 70.1 km/wk, with a peak of 228 cases/wk and the basic reproduction number (R0 ) was 3.1. The highest age-specific incidence rate was 228 per 100 000 in adults aged 50–54 y. Significantly more cases (79.4%) lived in rural areas compared with the general population (46.2%, p<0.0001). Five CHIKV clusters were detected. Likely spread was mostly by road, but a fifth of rural cases were spread by river travel. Conclusions: CHIKV initially spread quickly in rural areas mainly via roads, with lesser involvement of urban areas. Delayed spread occurred via river networks to more isolated areas in the rural interior. Understanding the patterns and timings of arboviral outbreak spread may allow targeted vector control measures at key transport hubs or in large transport vehicles.